Describing the Performance Satisfaction of Host Training Establishments on Accounting Student Trainees - Birondo, Chissa G; Miral, Nicole Shane H; Romaguera, Saagher E; Alfanta, Mylene P; Sumicad Jr, Eligen S (Faculty Of Islamic Economics and Business, 2024)
Purpose: This study aims to thoroughly evaluate the level of performance satisfaction displayed by accounting student trainees during their training in host establishments. The study focuses on three key dimensions: attendance and punctuality, knowledge and quality of work, and general attitude, in order to provide a detailed assessment of the trainees’ performance.Methodology: The study used a mixed-methods approach, specifically the sequential explanatory design. This involved the use of a survey questionnaire and in-depth interviews.Research Findings: The research findings indicate that the performance satisfaction of accounting student trainees is very satisfactory in terms of attendance and punctuality, with an overall mean rating of 3.63. Additionally, knowledge and quality of work are rated as very satisfactory, with an overall mean of 3.50. Their general attitude is also rated as very satisfactory, with an overall mean of 3.68. The qualitative data obtained through interviews provides a detailed examination of the trainees' strengths and weaknesses, along with valuable recommendations from the host training establishments. The strengths identified were independence, resourcefulness, and enthusiasm. However, two categories emerged as weaknesses, which are social awkwardness and inattentiveness. The host training establishments have advised accounting student trainees to be proactive, enhance their skills, seek opportunities and guidance, and be prepared. Tujuan Penelitian: Penelitian ini bertujuan untuk mengevaluasi secara menyeluruh tingkat kepuasan kinerja yang ditunjukkan oleh mahasiswa akuntansi selama pelatihan mereka di perusahaan tuan rumah. Studi ini berfokus pada tiga dimensi utama: kehadiran dan ketepatan waktu, pengetahuan dan kualitas kerja, dan sikap umum, untuk memberikan penilaian rinci terhadap kinerja peserta pelatihan.Metodologi: Penelitian ini menggunakan pendekatan metode campuran, khususnya desain penjelasan sekuensial. Hal ini melibatkan penggunaan kuesioner survei dan wawancara mendalam.Temuan Penelitian: Hasil penelitian menunjukkan bahwa kepuasan kinerja peserta pelatihan mahasiswa akuntansi sangat memuaskan dalam hal kehadiran dan ketepatan waktu, dengan nilai rata-rata keseluruhan sebesar 3,63. Selain itu, pengetahuan dan kualitas pekerjaan dinilai sangat memuaskan, dengan rata-rata keseluruhan 3,50. Sikap mereka secara umum juga dinilai sangat memuaskan, dengan rata-rata keseluruhan sebesar 3,68. Data kualitatif yang diperoleh melalui wawancara memberikan pemeriksaan rinci mengenai kekuatan dan kelemahan peserta, serta rekomendasi berharga dari lembaga penyelenggara pelatihan. Kekuatan yang diidentifikasi adalah kemandirian, akal, dan antusiasme. Namun ada dua kategori yang muncul sebagai kelemahan, yaitu kecanggungan sosial dan kurangnya perhatian. Lembaga pelatihan tuan rumah telah menyarankan mahasiswa akuntansi untuk bersikap proaktif, meningkatkan keterampilan mereka, mencari peluang dan bimbingan, dan bersiap.